The Effect of Return, Cost, Financing Factors and Risk on Profitability of Sharia Banks in Indonesia - Tanti Widia Nurdiani; Ruki Ambar Arum; Rahmat Putra Ahmad Hasibuan; Eddy Silamat; Samuel PD Anantadjaya (JEMSI (Jurnal Ekonomi, Manajemen, dan Akuntansi), 2023)
Some of the factors identified as influencing the profitability of Islamic banks include asset growth, volume of financing, low non-performing financing ratios, optimal financing distribution, large income spreads, low-cost funds, professional internal management, prudential principles in channeling financing, and several other factors that have an influence on the profitability of Islamic banking. This research is explanatory research (explanative research). Explanatory research seeks to explain the causal relationship between variables by testing hypotheses. The purpose of this research is to test the proposed hypothesis regarding the influence of the firm's fundamental variables on sharia stock prices as the dependent variable. This research is also quantitative. The quantitative approach is research related to quantitative data in the form of numbers that can be used with mathematical operations (Muhamad, 2008: 203). This study uses time series data with monthly data from January 2022 to June 2022. The focus of the research is the condition of all Islamic banking in Indonesia. Partially, the financing deposit ratio (FDR) has a positive and significant influence on the profitability of Islamic banking. This shows that the FDR ratio has a direct effect on the profitability of Islamic banking, because the FDR ratio is a ratio that describes a bank's ability to channel financing, and also describes the bank's liquidity. If the FDR is <80%, the bank will be burdened by profit sharing to third parties and additional Minimum Statutory Reserves (GWM) to Bank Indonesia, so that profitability is not optimal. On the other hand, if the FDR > 100%, it indicates that the bank's liquidity is disrupted.